Significance of Wharton’s jelly area in prediction of aberrant foetal growth - Amin, Sapna; Hebbar, Shripad; Pothakamuri, Deepika; Adiga, Prashant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Size of the baby at the time birth determines its outcome. Low birth weight babies have their own set of problems such as respiratory distress syndrome, hypoxic ischemic encephalopathy, metabolic derangements and high rates of admission to intensive care units. On the other hand too large babies may cause difficulty in vaginal births, higher incidence of birth trauma including the maternal genital injuries. Both conditions are associated with higher rates of operative delivery and hence it is important to investigate parameters which could identify these foetal growth abnormalities in the antenatal period only. The objective of the present investigation was to study the relationship between foetal umbilical cord Wharton’s Jelly Area and neonatal birth weight within two weeks of delivery Methods: A prospective observational study was conducted at Department of Obstetrics and Gynaecology, Kasturba Medical College, Manipal, Karnataka, India over a period of two years. Two hundred and fifty women from 34 weeks gestational age who have delivered within two weeks of estimation of Wharton’s Jelly Area by ultrasound were analysed. Wharton’s Jelly Area was measured in pregnant woman after 34 weeks of gestation at the time of third trimester scan. Scans were repeated every two weeks till the woman delivered. Measurements were done in a free loop of the umbilical cord. Regression analysis was used to correlate Wharton’s jelly quantity with the birth weight obtained after birth of the neonate. Results: There was a good correlation between Wharton’s Jelly Area and neonatal birth weight. The mean birth weight was 2247.2 gms in <than 10th centile group, 2945.1gms in 10th to 90th centile and 3552.1 gms in more than 90th centile group, demonstrating a consistent rise in mean birth weight with higher centile groups. Polynomial regression function showed good fit between Wharton’s jelly and birth weight (R² = 0.8842, p<0.001). When Wharton’s jelly area was less than 10th centile, 72% of neonates had small for gestational age (SGA). Conclusions: There is a positive association between Wharton’s Jelly Area and neonatal birth weight. Birth weight of neonate showed steady increase with increasing Wharton’s Jelly Area.